1979
DOI: 10.1136/adc.54.9.699
|View full text |Cite
|
Sign up to set email alerts
|

Folate nutrition and growth in infancy.

Abstract: SUMMARY The effect of suboptimal folate nutrition on the growing infant was studied in a population of infants fed a diet based on boiled, pasteurised cows' milk. One group of infants received a daily supplement of 1 mg folic acid from age 2 months, while the other group received a placebo. The infants were seen at bimonthly intervals. In the supplemented group the red cell folate level had increased to twice its pretreatment value by 4 months, and remained at this high level to the end of the first year. Hb c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 9 publications
(2 reference statements)
0
12
0
Order By: Relevance
“…In a systematic review, Lohner et al (2012) identified three intervention studies with folic acid in healthy infants receiving folic acid supplements (5-1 000 µg/day) and measuring serum folate (Hadler et al, 2008), red blood cell folate (Matoth et al, 1979) or both (Asfour et al, 1977). In a nonrandomised controlled trial, Asfour et al (1977) provided, for up to eight months, folic acid at 0, 5 or 10 µg/day in addition to a formula diet with a known folate concentration (196 µg/kg formula powder) to 20 Lebanese orphans weighing between about 3.5 and 8 kg and aged 2-11 months at the start of the study.…”
Section: Infants Aged 7-11 Monthsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review, Lohner et al (2012) identified three intervention studies with folic acid in healthy infants receiving folic acid supplements (5-1 000 µg/day) and measuring serum folate (Hadler et al, 2008), red blood cell folate (Matoth et al, 1979) or both (Asfour et al, 1977). In a nonrandomised controlled trial, Asfour et al (1977) provided, for up to eight months, folic acid at 0, 5 or 10 µg/day in addition to a formula diet with a known folate concentration (196 µg/kg formula powder) to 20 Lebanese orphans weighing between about 3.5 and 8 kg and aged 2-11 months at the start of the study.…”
Section: Infants Aged 7-11 Monthsmentioning
confidence: 99%
“…In a nonrandomised controlled trial, Asfour et al (1977) provided, for up to eight months, folic acid at 0, 5 or 10 µg/day in addition to a formula diet with a known folate concentration (196 µg/kg formula powder) to 20 Lebanese orphans weighing between about 3.5 and 8 kg and aged 2-11 months at the start of the study. In the studies by Hadler et al (2008) and Matoth et al (1979), no information is available on the intake of dietary folate and thus on total DFE intake. In the studies by Hadler et al (2008) and Matoth et al (1979), no information is available on the intake of dietary folate and thus on total DFE intake.…”
Section: Infants Aged 7-11 Monthsmentioning
confidence: 99%
“…[3][4][5] During pregnancy, it is linked to an increased risk of low birth weight and neural tube defects, 6,7 and it is also associated with stunting. 8,9 Vitamin B12 deficiency is more frequent in population with a poor or inadequate diet of animal foods. 10 Other causes of this deficiency include: intestinal parasitosis in low-income population, 11 Helycobacter pylori infections, 12 and atrophic gastritis in older adults (due to lack of intrinsic factor production).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In addition, a lack of folate may act as a limiting factor in weight gain and stature growth. [12][13][14] Studies also imply that iron plus folic acid supplementation can be justified based on the beneficial effects of these compounds on the cognitive and motor development in infants, [15][16][17] thereby reducing the risk of iron deficiency anemia. 18 The benefits and disadvantages of using different dosages of iron either alone or in combination have been investigated, but only partially, in relation to linear growth and weight gain.…”
Section: Introductionmentioning
confidence: 99%